2021
DOI: 10.1002/alz.057897
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory dysfunction and chronic cognitive impairment following SARS‐CoV‐2 infection in a sample of older adults from the Andes mountains of Argentina

Abstract: Background COVID‐19 has affected more than 150 million people. The causal coronavirus, SARS‐CoV‐2 has infected twice as many individuals who have remained asymptomatic. COVID‐19 includes central nervous system (CNS) manifestations and may result in chronic neuropsychiatric sequelae. Risk factors for COVID‐19 sequelae overlap with those for Alzheimer’s disease (AD), particularly older age and ApoE4 status. The Alzheimer’s Association Consortium on Chronic Neuropsychiatric Sequelae of SARS‐CoV‐2 infection (CNS S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Impairments in neurogenesis, which have been demonstrated in several neurodegenerative disorders, could contribute to hyposmia and neurodegeneration (Figure 1). Consistent with this notion, chronic cognitive impairment has been shown to correlate with olfactory dysfunction due to COVID-19 [10]. Hyposmia during acute COVID-19 was linked with increased vulnerability in memory functions in several studies [82][83][84].…”
Section: Neural Stem Cells Olfactory Function and Neurodegenerative D...mentioning
confidence: 68%
See 1 more Smart Citation
“…Impairments in neurogenesis, which have been demonstrated in several neurodegenerative disorders, could contribute to hyposmia and neurodegeneration (Figure 1). Consistent with this notion, chronic cognitive impairment has been shown to correlate with olfactory dysfunction due to COVID-19 [10]. Hyposmia during acute COVID-19 was linked with increased vulnerability in memory functions in several studies [82][83][84].…”
Section: Neural Stem Cells Olfactory Function and Neurodegenerative D...mentioning
confidence: 68%
“…The same study reported an incidence of anosmia in 18% of participants. An association exists between severity of cognitive impairment and severity of olfactory symptoms in older people recovering from COVID-19 [10].…”
Section: Introductionmentioning
confidence: 99%
“…But given the very large number of very different neurological disorders with very different etiologies, that possibility seems unlikely. Another possibility is that the olfactory loss precedes the neurological symptoms, which is the case for Alzheimer’s disease, Parkinson’s disease, the cognitive loss that can accompany long COVID, and depression ( Walker et al, 2021 ; Zamponi et al, 2021 ). Similarly, olfactory loss may precede all the disorders listed above and if olfactory loss precedes the cognitive, emotional, and motor symptoms, perhaps the olfactory loss plays a role in increasing the risk of developing these functional problems.…”
Section: Discussionmentioning
confidence: 99%
“…Increased risk of cognitive decline with loss of sense of smell—COVID as a recent example [ 135 , 136 ].…”
Section: Interventions—stimuli With Known Benefits On Cognitive Headr...mentioning
confidence: 99%